Analisis Partisipasi Anggota Terhadap Kinerja Keuangan pada Koperasi Serba Usaha Pegawai Balitbang Kemendikbud - Anisah Putri; Gladys Irenatasya; Intan Aulia Adibah; Marsyah Cahyani; Najwa Raihanah (LPPM Universitas Koperasi Indonesia, 2026)
The success of a cooperative is determined by the level of its members' participation because its business activities and capital turnover depend on the active contributions of members, from savings and transactions to service usage and involvement in decision making. Financial report data from the Koperasi Serba Usaha Pegawai Balitbang Kemendikbud shows a decrease in participation of 18.39% in 2024. This study aims to analyze how member participation affects the financial performance of cooperatives. The research method uses a descriptive qualitative method with a literature study approach. The research results show that the participation of members of the Koperasi Serba Usaha Pegawai Balitbang Kemendikbud affects business capital, which grew by 8.34%. However, the increase in capital was not accompanied by an increase in the residual business result, which actually decreased. This condition indicates that the increase in cooperative capital has not been utilized optimally.